Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.carbon.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defect-induced cooling on graphene hot-electron bolometers

Abstract: At high phonon temperature, defect-mediated electron-phonon collisions (supercollisions) in graphene allow for larger energy transfer and faster cooling of hot electrons than the normal, momentum-conserving electron-phonon collisions. Disorder also affects the heat flow between electrons and phonons at very low phonon temperature, where the phonon wavelength exceeds the mean free path. In both cases, the cooling rate is predicted to exhibit a characteristic cubic power law dependence on the electron temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…By using T 1 ∼1 μs (at 4.3 K) [32], we find P 1M ∼6×10 −17 W. If a monolayer of SMMs covers the whole graphene area, about 20 μm 2 for the smallest bowties, for an approximate SMM size of 1 nm, we estimate 2×10 7 SMMs covering the graphene and absorbing about 1.2 nW. This power is much higher (by at least two orders of magnitude) than the smallest absorbed power that we can measure with the graphene quantum dots [11,12,31], therefore power absorption from monolayer SMMs will cause a change in the power absorbed by the graphene quantum dots that should be easily measurable.…”
Section: Graphene Quantum Dot Bolometers and Their Operationmentioning
confidence: 69%
See 3 more Smart Citations
“…By using T 1 ∼1 μs (at 4.3 K) [32], we find P 1M ∼6×10 −17 W. If a monolayer of SMMs covers the whole graphene area, about 20 μm 2 for the smallest bowties, for an approximate SMM size of 1 nm, we estimate 2×10 7 SMMs covering the graphene and absorbing about 1.2 nW. This power is much higher (by at least two orders of magnitude) than the smallest absorbed power that we can measure with the graphene quantum dots [11,12,31], therefore power absorption from monolayer SMMs will cause a change in the power absorbed by the graphene quantum dots that should be easily measurable.…”
Section: Graphene Quantum Dot Bolometers and Their Operationmentioning
confidence: 69%
“…The mask is removed in the last step of the process by aqua regia, leaving the graphene fully exposed. Our previous work showed that the fabrication process modifies the graphene doping and quality [31]. The aqua regia is a strong hole dopant and affects the charge carrier density, while the metal sputtering induces defects in the graphene.…”
Section: Graphene Quantum Dot Bolometers and Their Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we can only measure the total thermal conductance, we note that it scales roughly linearly with the bath temperature. This indicates that the photonic thermal conductance [101] is dominating, since the phononic contribution scales as the bath temperature to the power ranging from 2 to 4 [102][103][104][105][106]. Electron diffusion also seems unlike due to the utilized superconducting leads that suppress this effect [99].…”
Section: Graphene Bolometermentioning
confidence: 99%